Analysis of polybrominated diphenyl ether and tetrabromobisphenol A in plastic samples in Mongolia - Bayarmaa, B; Gan-Erdene, T; Weber, Roland; Jargalsaikhan, L (Mongolian Journal of Chemistry, 2014)
This study was conducted to determine brominated flame retardants (BFRs) in electronic products in view compliance with the Restriction of Hazardous Substances (RoHS) and initiated by activities for implementation of the Stockholm Convention. Brominated flame retardants (BFRs) are synthetic additives mainly used in electrical and electronic appliances and in construction materials. Total 16 plastic casing samples were tested for threshold levels of polybrominated ethers. According the XFR results, the concentration of cadmium, lead, mercury and chromium were found below than Maximum Concentration Value (MCV) of RoHS, while the concentration of total bromine was exceeded the standard limitations in the samples. Only 1 out of the 16 plastic samples contains DecaBDEs while Tetrabromobisphenol (TBBP-A) is the major brominated flame retardants. However by the presence of one sample the average concentration of DecaBDE was above the RoHS limit of 1000 ppm as found in studies in other countries. DOI: http://doi.dx.org/10.5564/mjc.v15i0.317 Mongolian Journal of Chemistry 15 (41), 2014, p27-32